THE GAMIFICATION IN EDUCATION AND TRAINING: BASIC PRINCIPLES, REALIZATION AND TRENDS - Drozdova, Tatiana (Scientific practical conference, 2025)
The article is devoted to the implementation of the principals of gamification as an innovative approach in pedagogy. Gamification in education and training contributes to the creation of an extraordinary atmosphere in the educational process and strengthen motivation of students and helps to achieve real educational goals.